Psychological Impacts on Children Caused By Cases of Domestic Violence Against Women in Indonesia: Emergency of Violence in the Family and Household Security - Fadila, Oktami Nur (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2024)
Every human being is entitled to a sense of security and comfort in the form of love and protection within the family. However, recent cases of violence against women in Indonesia have reached emergency levels, violating human rights and categorized as crimes against the nature and dignity of humanity. The violence experienced by women is not only physical, but also involves psychological and emotional pressure and even sexual violence or marital rape. Ironically, cases of violence against women both physical and psychological have occurred since several years ago, and are accompanied by threats so that victims feel afraid to speak out. The occurrence of domestic violence, especially against women, has a significant impact on the psychological condition and development of children, which ultimately affects their future as adults. The trauma experienced by these children also affects their psychosocial conditions when interacting in their social environment. Children who often witness their parents arguing and violence committed by the father to the mother will be traumatized, making it difficult to make decisions when they grow up. Therefore, this should be a more serious concern for stakeholders, families and the surrounding community